From Eyewitness Narratives to Retellings and Literary Adaptations: The Russian Time of Troubles in Early Modern Europe - PROKHOROV, George (Anafora, 2023)
The article focuses on the adaptation strategies used by Lope de Vega in his play El Gran Duque de Moscovia y emperador perseguido (1617). This tragedy, built on material acquired from travelogues, represents the first depiction of the Russian Time of Troubles in fiction. In it, one can follow Lope de Vega’s shift from preserving the factual details collected from different travel sources to creating his own Baroque story placed within a purely Catholic world, as opposed to reality. In doing this, Lope de Vega creates a fictional space filled with mystery and miracles, where Heavens can intervene and punish the guilty party, whereby restoring the original status quo. Key situations turn from illustrations of an alien world into much more general depictions, namely, that of a tyrant versus a legal monarch, and the will of a ruler versus the law. The shift into tyranny provides the story with a new narrative centre and, by following Lope de Vega’s emphasis on the “Muscovian story,” discloses its universal spirit.